Subaxial transfacet fixation with/without laminectomy for cervical compressive myelopathy - Ahmed Ansari; Faiz Khan Yusufi; Nikhil Wadhwan (Romanian Neurosurgery)
Introduction. Cervical compressive myelopathy manifests mainly as spastic paralysis, exaggerated reflexes, and clumsiness of the hand, with/without gait disturbances. It mainly results from degenerative changes in cervical spine along with infolding of the ligamentum flavum, the presence of spondylolisthesis, the development of osteophytes, and the hypertrophy of facet joints. Though the recent pathology appears to be facetal instability, hence facetal fixation with or without laminectomy in these patients should be advocated.